Coordinated motion planning in a double-sided tools system with surface uniformity requirements. (October 2021) - Zhang, Kaiming; Liu, Yixin; Yao, Shulei; Liu, Shuang; Zhang, Xiancheng; Tu, Shantung
Abstract: Double-sided tools system is a promising design to counteract the forces caused by tools, and has become a practical way to machine thin-walled parts with the twisted structure. However, it is still difficult to obtain uniform machining effects on the part surfaces. This paper proposes a coordinated motion planning method for coordinating two tools in the double-sided tools system. The tools are devoted to guaranteeing the uniform surface quality while meeting the constraints about tools' velocity, tools' inclination and the system structure. At first, a velocity-dependent model is presented to describe the two tools' motions along the predefined paths. Then, the motion-planning problem of two tools is formulated as a constrained velocity-optimization problem, and the genetic algorithm is proposed to achieve the optimization target of the surface uniformity. Finally, experiments are performed on a real blade in a self-developed double-sided ultrasonic surface rolling process machine tool. The results demonstrate that the proposed coordinated motion planning method can effectively improve the surface uniformity in the double-sided tools system.